1997
DOI: 10.1002/(sici)1096-987x(19970730)18:10<1264::aid-jcc2>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

HUNTER: A conformational search program for acyclic to polycyclic molecules with special emphasis on stereochemistry

Abstract: A new conformational search program, HUNTER, connected with the force fields MMP2 and MM3(92) is presented. The program accepts all types of molecules with most different substructures, considers stereochemical facts, and covers conformational space efficiently and completely. The most important facilities are an automated analysis of the stereochemistry including topographical facts, a separate perturbation of the acyclic and cyclic parts of the molecule using modified corner flapping, and an incremental rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
1

Year Published

1999
1999
2002
2002

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 86 publications
1
6
0
1
Order By: Relevance
“…To confirm further the configuration of the sugar residue, the absolute energy minimum of 3 a was calculated by using the HUNTER program. [14] The coupling constants determined for the calculated conformation by using PCModel agreed well with the experimental values.…”
Section: Dedicated To Professor Wolfgang L¸ttkesupporting
confidence: 69%
See 2 more Smart Citations
“…To confirm further the configuration of the sugar residue, the absolute energy minimum of 3 a was calculated by using the HUNTER program. [14] The coupling constants determined for the calculated conformation by using PCModel agreed well with the experimental values.…”
Section: Dedicated To Professor Wolfgang L¸ttkesupporting
confidence: 69%
“…[13] This finding was used later by Wilke et al to explain the πnickel effect™ in the polymerization reaction of ethene on AlR 3 ; [14] in this context the reactions of organonickel complexes such as [Ni(bpy)Me 2 ] (bpy 2,2 À -bipyridine), [Ni(cdt)] (cdt cyclododeca-1,5,9-triene), and [NiCl 2 (PR 3 ) 2 ] with AlR 3 or AlHR 2 were also investigated. Wilke et al concluded that in these reactions thermolabile addition compounds of nickel core complexes were formed with AlR 3 or AlHR 2 .…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…B. in Spicamycintetraacetat11 ( 3 J =3.0 und 3.5 Hz) und Methyl‐4‐brom‐4,6‐didesoxy‐ α ‐ D ‐talopyranosid13 ( 3 J =1.5–4.1 Hz), bestätigt. Zur weiteren Absicherung der Konfiguration des Zuckers wurde mit HUNTER14 das absolute Energieminimum für 3 a gesucht. Eine Berechnung der Kopplungskonstanten mit PCModel ergab für die berechnete Konformation mit dem Experiment sehr gut übereinstimmende Werte.…”
unclassified
“…1,2,4,5-Tetracyclohexylcyclohexane ( 3 ) exists in seven stereoisomeric forms (three meso forms and two enantiomeric pairs, Scheme ) . Calculations of the TB/chair gaps of 1,2,4,5-tetracyclohexylcyclohexanes were performed with the MM3(92) program together with the HUNTER conformational search procedure (Table ) . As indicated by the calculations, the cis,syn,cis form is predicted to adopt a TB conformation.…”
mentioning
confidence: 99%